Periosteal Skeletal Stem Cells and Their Response to Bone Injury - Zhang, Nian; Hu, Liru; Cao, Zhiwei; Liu, Xian; Pan, Jian (Frontiers in Cell and Developmental Biology, 2022)
The bone exhibits remarkable ability of self-repair without fibrous scars. It is believed that the robust regenerative capacity comes from tissue-resident stem cells, such as the skeletal stem cells (SSCs). Roughly, SSC has two niches; one is the bone marrow (BM), and the other is the periosteum. BM-SSCs have been extensively studied for years. In contrast, our knowledge about periosteal SSCs (P-SSCs) is quite limited. There is abundant clinical evidence for the presence of stem cell populations within the periosteum. Researchers even successfully cultured “stem-like” cells from the periosteum in vitro. However, due to the lack of effective markers, it is hard to evaluate the stemness of real P-SSCs in vivo. Recently, several research teams have developed strategies for successful identification of P-SSCs. For the first time, we can assess the stemness of P-SSCs from visual evidence. The BM-SSCs and P-SSCs have a lot in common, but also share distinct properties. Here, we provide an updated review of P-SSCs and their particular responses to bone injury.